2014
DOI: 10.1021/jp504959z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemistry: The Effect of Dynamics

Abstract: Dynamical effects on the mechanochemistry of linear alkane chains, mimicking polyethylene, are studied by means of molecular dynamics simulations. Butane and octane are studied using density-functional theory (DFT), whereas higher homologues are studied using a simple one-dimensional model in which the molecules are represented by a linear chain of Morse potentials (LCM). The application of a fixed external force to a thermodynamically pre-equilibrated molecule leads to a preference for cleavage of the termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 40 publications
5
28
0
Order By: Relevance
“…Here, the application of mechanical forces on a system alters the potential energy surface (PES), and consequently, reaction pathways and rates. The effects of external forces were recently investigated for several different systems . Moreover, recent reviews were also published on the topic of mechanochemistry .…”
Section: Introductionmentioning
confidence: 99%
“…Here, the application of mechanical forces on a system alters the potential energy surface (PES), and consequently, reaction pathways and rates. The effects of external forces were recently investigated for several different systems . Moreover, recent reviews were also published on the topic of mechanochemistry .…”
Section: Introductionmentioning
confidence: 99%
“…Uggerud and coworkers used EFEI-based MD simulations in conjunction with DFT calculations and models consisting of a chain of Morse potentials to study the basic features of mechanochemical processes under dynamic conditions [104]. The results of this study showed that the simple model consisting of Morse potentials is adequate for describing the F-dependent dynamics of polymers, which may reduce the computational costs of simulations of mechanochemical processes.…”
Section: Application Of F Between Atomsmentioning
confidence: 94%
“…Of course, which of the two equal y ‐bonds breaks first depends on the thermal noise in reality and may also depend on nonequilibrium effects which may be described by a Franck–Condon theory of mechanochemistry . The effects of thermal fluctuations have already been demonstrated to play a key role in mechanochemistry . As a real chemical example we have the flattening of the OSiO bond angles in siloxanes, see for example, Refs.…”
Section: Case Of a Planar 4‐atomic Abba Molecule With C 2h Symmetrymentioning
confidence: 99%
“…[13] An algorithm to locate optimal BBPs has been recently proposed. [66] Note that a bond will actually break before the BBP due to finite temperature effects [67][68][69] or by the zero point energy of the corresponding bond. The kinetics of the break caused mainly by the force can be explained by a usual escape of the molecular state over the decreasing barrier.…”
Section: Application Of Newton Trajectoriesmentioning
confidence: 99%
See 1 more Smart Citation